Why Don’t They Leave? Reasons for the Immobility of Young Adults Remaining in Villages in Deprived Areas - Czibere Ibolya; Lonczák Noémi (European Countryside)
The reasons for immobility in a rural space are not self-evident in previous literature and research. Through our qualitative research, we aim to contribute to explanations for staying in less-favoured rural areas, by taking into account indicators such as job and income opportunities, local ties, community characteristics and patterns of contact networks. Furthermore, we investigated the presence of immobility types (involuntary immobility; voluntary immobility; and acquiescent immobility) introduced among two social groups with different characteristics (high and low social status youth). The research is based on 104 semi-structured interviews (53 with the young and 51 with their parents) in 15 small eastern Hungarian villages with a population of less than 2,500 people. One of the key findings of the study was to identify the different explanatory factors behind the decision to stay with two types of young people. The study can serve as a tool for the development of rural population policies.